Implementation of the Protocoler's Role on Facilitating the Agenda of the Regional Head - Ade Guruh Diputra; Sri Hartini Jatmikowati; Wahyu Wiyani (Innovation Business Management and Accounting Journal, 2025)
This study aims to analyze the role of the Protocol Section in facilitating the Regional Head's agenda, as well as identifying inhibiting and supporting factors that affect its performance. The research was conducted in the Protocol Section of Pasuruan City at the Regional Secretariat Office of Pasuruan City, Panggungrejo District, Pasuruan City, East Java Province. The data analysis technique in this study used descriptive qualitative analysis. This research found that the Pasuruan City Protocol and Leadership Communication Section has a strategic role in supporting the Regional Head's agenda and creating a positive image of the government. Based on Perwali Number 53 of 2022, this section has carried out the tasks of leadership facilitation, guest management, agenda preparation, and government communication. With an achievement of 90% of the annual target and completion of 107 out of 112 service requests, the effectiveness of this section's work is relatively high. The evaluation of the Regional Government Work Plan (RKPD) for the fourth quarter of 2024 also showed good performance, including budget management. However, challenges remain in improving human resources, SOP-based discipline, and optimizing regulations. Increased transparency, archive systems, and effective communication are needed to strengthen government professionalism. Regular evaluation and modern management are needed to improve the effectiveness and transparency of governance. This research is expected to help the Protocol and Communication Section of Pasuruan City Leaders improve human resources through continuous training, including event management, protocol, and readiness to face urgent situations. In addition, using technology can improve efficiency, communication, transparency, and governance accountability.